Does newspaper coverage influence or reflect public perceptions of the economy?. (October 2017) - Hopkins, Daniel J.; Kim, Eunji; Kim, Soojong
Citizens' economic perceptions can shape their political and economic behavior, making the origins of those perceptions an important question. Research commonly posits that media coverage is a central source. Here, we test that prospect while considering the alternative hypothesis that media coverage instead echoes public perceptions. This paper applies a straightforward automated measure of the tone of economic coverage to 490, 039 articles from 24 national and local media outlets over more than three decades. By matching the 245, 947 survey respondents in the Survey of Consumer Attitudes and Behavior to measures of contemporaneous media coverage, we can assess the sequencing of changes in media coverage and public perceptions. Together, these data illustrate that newspaper coverage does not systematically precede public perceptions of the economy, a finding which analyses of television transcripts reinforce. Neither national nor local newspapers appear to strongly influence economic perceptions.